Doing Critical Health Communication: Negotiating the Terrain of Transdisciplinary Collaboration - Kline, Kimberly N.; Khan, Shamshad (Frontiers in Communication, 2019)
In this article, we think about how critical health communication scholars can speak to audiences outside the discipline in order to make an impact on public health and policy, health promotion, and health care delivery. We take into consideration how are we situated in our relationship with transdisciplinary research as well as the challenges and opportunities involved in collaborating with transdisciplinary teams including the ways we can navigate the inherent method/ological tensions in such collaborations. We focus on how the methodological considerations of “critical” health scholarship are situated vis-à-vis the epistemic status quo commitments in the disciplines of our potential allies.